Factors of Infertility among the Males in Selected Hospitals of Dhaka City - Quadir, SA Anowar ul; Islam, Khan Nazrul; Alam Babul, Md Safiul; Akhter, Jesmin; Bari, Mohammad Abdul (Bangladesh Journal of Urology, 2022)
Background: Infertility is a global health issue affecting approximately 8-10% of couples and has multidimensional problem with social, economic and cultural implications, which can take threatening proportions in countries with strong demographic problems. Reproductive health in Bangladesh focused mainly on women health and ignoring the role of men, in spite of the important role that men are playing in reproduction and fertility which impact his family and environment. Objective: To find out the factors of infertility among the males in selected hospitals of Dhaka city. Methods: A convenience sample of 112 medical records for males diagnosed with infertility in Shaheed Suhrawardi Medical College Hospital, National Institute of Kidney Diseases and Urology, Sher-E-Bangla Nagar, Dhaka, Fertility center Mohammedpur Dhaka, Infertility care and Research Center Mohammedpur Dhaka were retrospectively reviewed for the cause of their infertility. Four months duration of study from May 2016 to August 2016. After completion of data collection, the collected data was checked and verified on regular basis for accuracy, consistency and completeness. Data was edited and coded. The results were presented into the form of tables and figures. Data was processed in computer by using the software SPSS, version 22 and statistical analysis was done. Results: Male factor alone was accounted for 52% of infertility among couples of these 90 had primary infertility and 22 had secondary infertility. The mean duration of infertility was 4.98±3.99 years and the mean age for male cases was 33.5±7.24 years The most common causes among infertile men were, idiopathic infertility 36.6%, varicocele 32.1%, obstruction of the seminal tract 18.8%, and hormonal problems 5.4%. Least common causes found were, medication 1.8%, spinal cord injury 1.8%, cryptorchidism 1.8%, and testicular failure 1.8%. Conclusion: More than half of the infertile couples were from an idiopathic cause. Study results confirm that understanding about male reproductive function and the environmental factors that affect it is insufficient. Provide education to infertile men by doctors in charge about potential risk factors that may affect fertility and not just provide treatment because simple changes in lifestyle can improve fertility. Bangladesh J. Urol. 2021; 24(1): 37-45